Macroeconomic fluctuations and bank lending: evidence for Germany and the euro area - Sandra Eickmeier; Boris Hofmann; Andreas Worms (Deutsche Bundesbank, 2006)
This paper analyzes how bank lending to the private nonbank sector responds dynamically to aggregate supply, demand and monetary policy shocks in Germany and the euro area. The results suggest that the dynamic responses in the two areas are broadly similar, although there are some differences in the relative contribution of the three shocks to the development of output, prices, interest rates and bank loans over time. In order to assess the role of bank lending in the transmission of macroeconomic shocks, we perform counterfactual simulations and analyze the dynamic responses of German loan sub-aggregates in order to test the distributional implications of potential credit market frictions. The results suggest that there is no evidence that loans amplify the transmission of macroeconomic fluctuations or that a "financial accelerator" via bank lending exists.
Keywords: G21; E32; E44; 330; Business cycle fluctuations; bank lending; SVAR model; sign restrictions; Kreditgeschäft; Schock; Konjunktur; Transmissionsmechanismus; Schätzung; Deutschland; EU-Staaten